The Role Of Corporate Communication In Enhancing The Performance Of The Human Resource From The Employees’ Point Of View (Journal of Namibian Studies : History Politics Culture, 2023)
The purpose of This research paper is to measure the role of corporate communication in enhancing the performance of the human resource and drop it on a level  of the hospital under study.In order to achieve this, a questionnaire was designed and distributed in its final form to a sample of 54 individuals, We relied on the Statistical Package for the Social Sciences (SPSS) for the purpose of analyzing data, testing hypotheses, and drawing conclusions.The study reached several results, the most important of which are: the availability of corporate communication requirements from the point of view of the study sample members; There is also a statistically significant effect of corporate communication on the performance of the human resource from the point of view of the study sample members.